2016
DOI: 10.2147/ott.s96133
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of advanced malignant fibrous histiocytoma of the right forearm with apatinib: a case report

Abstract: Malignant fibrous histiocytoma (MFH) is the most common soft-tissue sarcoma in late adult life. Unfortunately, advanced MFH has a poor prognosis due to a lack of effective drugs. We present here a case of advanced MFH with partial response to apatinib, a new potent oral small-molecule tyrosine kinase inhibitor targeting the intracellular domain of vascular endothelial growth factor receptor 2 (VEGFR-2). To the best of our knowledge, this is the first case report using apatinib for MFH. Quantitative polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…A 78-y-old patient with metastatic fibrous histiocytoma received apatinib, and a PR was achieved. 6 The tumor did not progress 6 months after treatment. A 68-y-old patient who was diagnosed with advanced multiple intra-abdominal and pelvic round cell liposarcoma with liver metastasis also got a PR following apatinib administration.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A 78-y-old patient with metastatic fibrous histiocytoma received apatinib, and a PR was achieved. 6 The tumor did not progress 6 months after treatment. A 68-y-old patient who was diagnosed with advanced multiple intra-abdominal and pelvic round cell liposarcoma with liver metastasis also got a PR following apatinib administration.…”
Section: Discussionmentioning
confidence: 93%
“…Promising efficacy of apatinib was reported in several subtypes of sarcomas. [6][7][8][9][10] We further retrospectively investigated the outcomes of apatinib in 31 patients with advanced metastatic or recurrent sarcoma who pretreated with at least one chemotherapy regimen or refused to receive chemotherapy. in 7 patients (22.6%) and trunk in 3 patients (9.7%).…”
Section: Introductionmentioning
confidence: 99%
“…With a favorable side-effect profile and improved outcomes, apatinib has been shown to be a new therapeutic option in a variety of tumor types. 4 , 9 However, successful use of apatinib in angiosarcomas has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Its application is being extended for treating non-small-cell lung, breast, and hepatocellular cancers in phase II and III clinical trials across the People's Republic of China. Some case reports have also shown that apatinib has antitumor efficacy against soft tissue sarcoma [ 14 16 ]. It is worth noting that anti-angiogenic therapies may work synergistically with conventional chemotherapy treatments [ 17 – 19 ].…”
Section: Introductionmentioning
confidence: 99%